PEGylation of Guanidinium and Indole Bearing Poly(methacrylamide)s - Biocompatible Terpolymers for pDNA Delivery - Cokca, Ceren; Hack, Franz J.; Costabel, Daniel; Herwig, Kira; Huelsmann, Juliana; Then, Patrick; Heintzmann, Rainer; Fischer, Dagmar; Peneva, Kalina (Macromolecular Bioscience, 2021)
This study describes the first example for shielding of a high performing terpolymer that consists of N-(2-hydroxypropyl)methacrylamide (HPMA), N-(3-guanidinopropyl)methacrylamide (GPMA), and N-(2-indolethyl)methacrylamide monomers (IEMA) by block copolymerization of a polyethylene glycol derivative - poly(nona(ethylene glycol)methyl ether methacrylate) (P(MEO(9)MA)) via reversible addition-fragmentation chain transfer (RAFT) polymerization. The molecular weight of P(MEO(9)MA) is varied from 3 to 40 kg mol(-1) while the comonomer content of HPMA, GPMA, and IEMA is kept comparable. The influence of P(MEO(9)MA) block with various molecular weights is investigated over cytotoxicity, plasmid DNA (pDNA) binding, and transfection efficiency of the resulting polyplexes. Overall, the increase in molecular weight of P(MEO(9)MA) block demonstrates excellent biocompatibility with higher cell viability in L-929 cells and an efficient binding to pDNA at N/P ratio of 2. The significant transfection efficiency in CHO-K1 cells at N/P ratio 20 is obtained for block copolymers with molecular weight of P(MEO(9)MA) up to 10 kg mol(-1). Moreover, a fluorescently labeled analogue of P(MEO(9)MA), bearing perylene monoimide methacrylamide (PMIM), is introduced as a comonomer in RAFT polymerization. Polyplexes consisting of labeled block copolymer with 20 kg mol(-1) of P(MEO(9)MA) and pDNA are incubated in Hela cells and investigated through structured illumination microscopy (SIM).
CRIS-Team WoS Importer:2021-08-06